"Police, Public Safety, and Race‐Neutral Discourse". Issue 6 (10th June 2013) - Nuño, Luis F.
Abstract In the final decades of the 20th century policing in America was refashioned in the public image of community policing. Race‐neutral discourses dominate public and professional support for community‐oriented policing philosophies. In the contemporary era of hyper‐incarceration a focus on ethnoracial divisions grounded in the sociology of peculiar institutions is essential for documenting transformations in how the municipal police services are legitimized. Here I analyze how the public discourses of law‐and‐order center on distortions of social fact and public safety. Today the criminalization of immigrants is the latest turn in public discourses shaping patterns of ethnoracial visions and divisions. The carceral breadth of the neoliberal penal state extends beyond social structure, repackaged as race‐neutral ideology across the public sphere.